European Society of Endodontology position statement: External Cervical Resorption. (26th September 2018) - ,; Patel, S.; Lambrechts, P.; Shemesh, H.; Mavridou, A.
Abstract: This Position Statement represents the consensus of an expert committee convened by the European Society of Endodontology (ESE) on External Cervical Resorption (ECR). The statement is based on current clinical and scientific evidence as well as the expertise of the committee. The primary aim is to provide a current authoritative position on the aetiology, histopathology, clinical presentation and management of ECR, and also to highlight areas where there is minimal evidence. Previously published review articles provide more detailed background information and the basis for this position statement ( International Endodontic Journal 51, 1205, 2018, International Endodontic Journal 51, 1224, 2018). It is intended that this position statement will be updated at appropriate intervals, as further evidence emerges.